The Rolf Method of Structural Integration on Fascial Tissue Stiffness, Elasticity, and Superficial Blood Perfusion in Healthy Individuals: The Prospective, Interventional Study - Jędrzejewski, Grzegorz; Kasper-Jędrzejewska, Martyna; Dolibog, Paweł; Szyguła, Renata; Schleip, Robert; Halski, Tomasz (Frontiers in Physiology, 2020)
Introduction: There are multiple theories surrounding the physiological impact of structural integration (SI) with little evidence or research corroborating any of these. The aim of the study was to assess the effectiveness of 10 sessions of SI on fascial tissue (FT) superficial blood perfusion, stiffness, and elasticity in 13 healthy women. Methods: This was a prospective, interventional study. The primary outcome measures were FTs’ superficial blood perfusion, stiffness, and elasticity of bilateral selected FT points on the body. Data were collected before and after 10 sessions of SI intervention. Statistical analysis was performed using the non-parametric Wilcoxon test (intragroup comparison). Results: The superficial blood perfusion increased significantly in the most selected FT points on the body (p < 0.05). SI interventions produced significant decreases in selected points (brachioradialis, biceps brachii, and trapezius; p < 0.05) of FT stiffness and significant increases in elasticity (brachioradialis, biceps brachii, triceps surae, and trapezius; p < 0.05), especially in the FT of the right (dominant) upper limb. Conclusion: A 10-session of SI demonstrated positive effects on increasing superficial blood perfusion contributed to a decrease in FT stiffness and an increase in elasticity properties in the dominant upper limb. Data collection for this study is currently underway, and the trial is registered at ISRCTN.com with the identifier: ISRCTN46707309.